Temperature Extremes and Sex-Related Physiology, Not Environmental Variability, Are Key in Explaining Thermal Sensitivity of Bimodal-Breathing Intertidal Crabs - Jimenez, Pedro J.; Vorsatz, Lyle D.; Costa, Tânia M. [UNESP]; Cannicci, Stefano (Frontiers, 2022)
Global temperature increases are predicted to have pronounced negative effects on the metabolic performance of both terrestrial and aquatic organisms. These metabolic effects may be even more pronounced in intertidal organisms that are subject to multiple, abruptly changing abiotic stressors in the land-sea transition zone. Of the available studies targeting the intertidal environment, emphasis has largely been on water-breathing model organisms and this selective focus resulted in limited reliable forecasts on the impact of global warming on primarily air-breathing intertidal species. We investigated the thermal sensitivity of six phylogenetically related fiddler crab species that occupy different microhabitats on intertidal shores from south America and east Asia to test how bimodal-breathing intertidal ectotherms cope with thermal stress. We examined the metabolic physiology and thermal limits of the crabs by measuring their cardiac function and oxygen consumption along a thermal gradient. Their specific thermal microhabitat was also appraised. We found that subtropical fiddler crab species inhabiting vegetated microhabitats have lower upper lethal temperatures and therefore greater thermal sensitivity in comparison to their tropical counterparts. Additionally, females exhibited higher oxygen consumption and lower lethal temperatures in comparison to males. Our results contradict previous predictions that species from higher latitudes that experience greater temperature variability have broader latitudinal distributions, greater phenotypic plasticity and lower thermal sensitivity. Furthermore, the higher thermal sensitivity demonstrated by female fiddler crabs with respect to males strongly suggests a role of both gametogenesis and physiological dimorphism on the thermal performance of tropical and subtropical intertidal organisms. These observations ultimately, advocates for further studies on sex-biased and development-biased thermal sensitivity before drawing any generalizations based on a single sex or life stage.
Keywords: bimodal breathers; fiddler crabs; habitat temperature; intertidal organisms; latitudinal gradient; thermal adaptations; thermal physiology